Urban air pollution and emergency room admissions for respiratory symptoms: a case-crossover study in Palermo, Italy - Calamusa Giuseppe; Vultaggio Marcello; Cerame Giuseppe; Cusimano Rosanna; Tramuto Fabio; Maida Carmelo M; Vitale Francesco (BMC, 2011)
Abstract Background Air pollution from vehicular traffic has been associated with respiratory diseases. In Palermo, the largest metropolitan area in Sicily, urban air pollution is mainly addressed to traffic-related pollution because of lack of industrial settlements, and the presence of a temperate climate that contribute to the limited use of domestic heating plants. This study aimed to investigate the association between traffic-related air pollution and emergency room admissions for acute respiratory symptoms. Methods From January 2004 through December 2007, air pollutant concentrations and emergency room visits were collected for a case-crossover study conducted in Palermo, Sicily. Risk estimates of short-term exposures to particulate matter and gaseous ambient pollutants including carbon monoxide, nitrogen dioxide, and sulfur dioxide were calculated by using a conditional logistic regression analysis. Results Emergency departments provided data on 48,519 visits for respiratory symptoms. Adjusted case-crossover analyses revealed stronger effects in the warm season for the most part of the pollutants considered, with a positive association for PM10 (odds ratio = 1.039, 95% confidence interval: 1.020 - 1.059), SO2 (OR = 1.068, 95% CI: 1.014 - 1.126), nitrogen dioxide (NO2: OR = 1.043, 95% CI: 1.021 - 1.065), and CO (OR = 1.128, 95% CI: 1.074 - 1.184), especially among females (according to an increase of 10 μg/m3 in PM10, NO2, SO2, and 1 mg/m3 in CO exposure). A positive association was observed either in warm or in cold season only for PM10. Conclusions Our findings suggest that, in our setting, exposure to ambient levels of air pollution is an important determinant of emergency room (ER) visits for acute respiratory symptoms, particularly during the warm season. ER admittance may be considered a good proxy to evaluate the adverse effects of air pollution on respiratory health.